Design of Interactive Learning Media Using Google Sites Assisted Inquiry Learning to Improve Critical Thinking Ability of Studets at SMAN 2 Painan - M. Al Fadhiel; Festiyed Festiyed; Desnita Desnita; Fuja Novitra (Physics Learning and Education, 2025)
The development of 21st-century technology demands more interactive and student-centered learning. However, preliminary studies at SMAN 2 Painan showed that students' critical thinking skills on heat were still low. This was due to the teacher-centered learning style, which resulted in students being less active, and the media used did not support exploration and discovery of concepts. To address these issues, this study developed an interactive, inquiry-based learning media supported by Google Sites. The development process followed the Dick and Carey model, with expert validation and practicality testing on 30 students and 3 Physics teachers. The validation results showed a Cohen's Kappa value of 0.96 (very valid), while the practicality test produced a value of 0.88 (very practical). These findings suggest that Google Sites can be an effective alternative to support inquiry-based learning and improve students' critical thinking skills. Consequently, this media can be used as an adaptive and accessible digital learning innovation. However, this study was limited to a small sample size, focused on only one topic, and did not examine the long-term impact of media use.